\(\frac{49.3^3-15^2.7+7.81}{3.15^2-10^3}\)

">
K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

29 tháng 6 2016

\(=\frac{7^2.3^3-3^2.5^2.7+7.3^4}{3.3^2.5^2-2^3.5^3}\)\(=\frac{7.3^2\left(7.3-5^2+3^2\right)}{5^2\left(3^3-2^3.5\right)}\)\(=\frac{7.3^2.5}{5^2.\left(-13\right)}=\frac{7.3^2}{5.\left(-13\right)}=\frac{63}{-65}\)

6 tháng 7 2017

\(a.\left(\frac{-2}{3}+\frac{4}{15}\right)^3=\left(\frac{-10+4}{15}\right)^3=\frac{-6^3}{15}=\frac{-8}{125}\)

\(b.\left(\frac{3}{21}-\frac{2}{7}\right)^2=\left(\frac{3}{21}-\frac{6}{21}\right)^2=\frac{-1}{7}^2=\frac{-1}{49}\)

\(d.3-\left(-3.15\right)^0+\left(0.5\right)^2:2=3-1+0.25=2+0.25=2.25\)

\(e.81-3^2:\left(0.375\right)^2=81-9:0.140625=81-64=17\)

6 tháng 7 2017
  • a) =\(\left(\frac{-10}{15}+\frac{4}{15}\right)^3\)=\(\left(\frac{-6}{15}\right)^3\) = \(\left(\frac{-2}{5}\right)^3\) =\(\frac{-8}{125}\)

b) \(=\left(\frac{3}{27}-\frac{6}{21}\right)^2=\left(\frac{-3}{21}\right)^2=\left(\frac{-1}{7}\right)^2=\frac{1}{49}\)

 d) \(=3-1+1:2=2+\frac{1}{2}=\frac{5}{2}\)

e) \(=81-9:\left(\frac{3}{8}\right)^2=72:\frac{9}{64}=72.\frac{64}{9}=512\)

28 tháng 12 2015

\(x=\frac{10^2.5^3.15^6}{3^6.5^{10}}=\frac{\left(2.5\right)^2.5^3.\left(3.5\right)^6}{3^6.5^{10}}=\frac{2^2.5^2.5^3.3^6.5^6}{3^6.5^{10}}=\frac{2^2.5^{11}.3^6}{3^6.5^{10}}=2^2.5=4.5=20\)

Vậy x=20.

26 tháng 6 2019

1. sai dấu nhé 

2.a, \(\frac{45^{10}.5^{20}}{75^{15}}=\frac{\left(3^2.5\right)^{10}.5^{20}}{\left(5^2.3\right)^{15}}=\frac{3^{20}.5^{30}}{5^{30}.3^{15}}=3^5=243\)

b, \(\frac{\left(0,8\right)^5}{\left(0,4\right)^6}=\frac{\left(\frac{4}{5}\right)^5}{\left(\frac{2}{5}\right)^6}=\frac{\left(\frac{2}{5}\cdot2\right)^5}{\left(\frac{2}{5}\right)^6}=\frac{\left(\frac{2}{5}\right)^5\cdot2^5}{\left(\frac{2}{5}\right)^5\cdot\frac{2}{5}}=2^5\div\frac{2}{5}=32\cdot\frac{5}{2}=80\)

c, \(\frac{2^{15}.9^4}{6^6.8^3}=\frac{2^{15}.3^8}{2^6.3^6.2^9}=\frac{2^{15}.3^2}{2^{15}}=3^2=9\)

18 tháng 8 2018

\(M=\frac{5}{2\cdot7}+\frac{4}{7\cdot11}+\frac{3}{11\cdot14}+\frac{1}{14\cdot15}+\frac{13}{15\cdot28}\)

\(M=\frac{1}{2}-\frac{1}{7}+\frac{1}{7}-\frac{1}{11}+...+\frac{1}{15}-\frac{1}{28}\)

\(M=\frac{1}{2}-\frac{1}{28}\)

\(M=\frac{13}{28}\)